The health practices of the Mansaka families and their implications to health education - Cases, Perla Obordo 1938- (s.n.], 1972)
This study concerning the Mansaka, a culture group living in the hinterlands of Davao del Norte was done to determine the difficulty of influencing effectively health knowledge, attitudes, and practices in a school and community of people with varied cultural background. The study of the health practices of the Mansaka families may help in identifying the specific health needs of the Mansakas and may serve as guide for health innovators in planning and implementing functional health programs in the area.